Anomalous Capacitance Behavior of Sol-Gel Deposited V2O5 Film on Crystalline Silicon - Bulgurcuoglu, A. E.; Gokdemir, F. P.; Ozdemir, O.; Kutlu, K. (AMER SCIENTIFIC PUBLISHERS, 2017)
Sol-gel produced vanadium pentoxide (V2O5) thin film was grown over differently doped crystalline silicon (p/n c-Si) substrates and electrical characteristics were investigated through current-voltage (I-V) and capacitance-voltage (C-V) measurements within dark and light ambient. For the film over p-c-Si, capacitance behavior was explained in terms of semiconductor (V2O5)/native oxide (SiO2)/semiconductor (p-c-Si) [SIS] structure in which existence of SiO2 insulator film was verified through infrared (IR) measurement. For the film over n-c-Si, negative capacitance or inductance phenomenon, corresponded to space charge limited current regime in I-V analysis, was observed and the derived admittance expression for such issue was successfully applied for the present structure.
Keywords: V2O5; Sol-Gel; SIS; Admittance; Negative Capacitance; FTIR; VANADIUM PENTOXIDE; THIN-FILMS; OPTICAL-PROPERTIES; CELLS; PHOTOOXIDATION; CONDUCTION; TRANSPORT; DEVICES; Engineering; Science & Technology - Other Topics; Physics